Central bank communication and correlation between financial markets: Canada and the United States - Melanie-Kristin Beck; Bernd Hayo; Matthias Neuenkirch (Philipps-University Marburg, Faculty of Business Administration and Economics, 2012)
We study the correlation between pairs of bond and stock markets in Canada and the United States between January 1998 and December 2006 in the framework of Diagonal-BEKK models. Our research question is whether monetary policy action and communication by the Bank of Canada and the Federal Reserve significantly affect the co-movement of financial markets. We find that target rate changes and various forms of communication by both central banks increase correlations within Canadian bond and stock markets as well as between Canadian and US financial markets.
Keywords: E52; F30; G12; G15; 330; Bank of Canada; Central Bank Communication; Diagonal-BEKK models; dynamic correlations; Federal Reserve; financial markets; Geldpolitik; Informationsverhalten; Öffentlichkeitsarbeit; Börsenkurs; Aktienmarkt; Rentenmarkt; Korrelation; Schätzung; Kanada; USA